The Development Of An Intergrated Model For Amil Zakat - Abdulsoma, Thoarlim; Azman, Ab Rahman; Ahmad Anis, Mohd Fauzi (2016)
Amil zakat (zakat collector) is an individual that is responsible in the collection of zakat or tithes. Generally amil is appointed by the state Islamic religious council by which most of them do not have specific background in religious knowledge or in the field of zakat. Nevertheless there were several cases on breach of trust among the current amilwhich affect the credibility and trust of Islamic society towards zakat institutions in Malaysia. The objective of the research is to determine the course and training provided to the zakat collector besides analysed the content of the course and training given to the zakat collector. This research applied the quantitative research methodology which is field study using interviews methods and qualitative using the documentation research in the form of deductive and inductive methods. The finding of the research indicated that there are no specific courses or trainings provided to the amil zakat after their appointment and commissioning. It can be concluded that there is vital need to enhance the role of zakat collector through the effective course and training. The implication of the research is it can improve the weakness of the existing amil zakat management system in each state in Malaysia thus assisting in decreasing and handling of misconduct cases involving amil zakat. Thus it is highly recommended to implementamil professional certification program that consist of 10 specific modules specifically for certified amil which emphasize on the integrity and skills from various aspect such as communication, missionary endeavour, sermon and leadership.